ASSIGNMENT OF THE CONTRACT. A SPECIAL CASE IN THE MATTER OF THE INSURANCE CONTRACT - Ștefan Matei DĂNILĂ (Challenges of the Knowledge Society)
Special situations may arise in the relations between the contracting parties, which may lead to a substitution of the party in the insurance relations - the assignment of the insurance contract With regard to the assignment of the insurance contract, each party may substitute a third party for its insurance relations. The general provisions on assignment, namely those provided by Art. 1315 and Art. 1316 of the Civil Code and those of Art. 1566-1586 Civil Code on the assignment of debt, the special provisions of Art. 2212 Civil Code in the matter of the insurance contract, together with the provisions of the special legislation, such as Law no. 190/1996 on the mortgage contract for real estate investments, provide the regulatory framework necessary to carry out the operation. In terms of insurance, in accordance with the provisions of Art. 2212 of the Civil Code – “Assignment of insurance”, the insurer may assign the insurance contract only with the written consent of the insured. The doctrine has shown that the assignment contract inserted in an insurance contract can be consensual, but it is necessary, ad probationem, that the agreement of the other party regarding the assignment take the written for The concrete legal conditions under which the assignment of the insurance contract may occur will be analyzed subsequently, with various solutions of the courts being commented upon in context.